Relationship between children's and parents' blood pressure - Desy Aswira Nasution; Rusdidjas Rusdidjas; Supriatmo Supriatmo; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti Siregar (Indonesian Pediatric Society Publishing House, 2014)
Background A family history of hypertension is a risk factor for hypertension in children. Past studies have reported a significant relationship between elevated blood pressure in children and hypertensive parents. Objective To assess for an association between blood pressure in children and that of their parents. Methods A cross-sectional study was conducted in 90 children aged 6-18 years in Baringin Village, Panyabungan, from May to June 2010. Subjects were collected by consecutive sampling. Classification of hypertension was based on Fourth Task Force Guidelines by measuring blood pressure, height, and weight. We used Student's T-test to analyze numerical data. Simple linear regression was used to investigate the relationship between blood pressures of children and their parents. Results Of the 90 participants recruited, 24 boys and 17 girls had hypertensive parents. The mean systolic (SBP) , diastolic (DBP) and arterial blood pressure (MABP) were significantly higher in children with hyperten sive parents than in children with normotensive parents [ (SBP 116. 7 (SD 7 .07) vs. 87 .1 (SD 13.57) mmHg; P=0.0001), (DBP 77.8 (SD 8.33) vs. 51.8 (SD 11.70) mmHg; P=0.0001), (MABP 90.7 (SD 7.41) vs . 63 .6 (12.10) mmHg; P=0.000 1] . There was a significant relationship between elevated SBP in boys and their fathers, as indicated by the correlation coefficient (r =0.806; P=0.0001). Conclusion The blood pressure is significantly higher in children with hypertensive parents than in those with normotensive parents. There is a correlation between SBP in boys and that of their fathers.